Computed tomographic appearance of transcaval ureter in two dogs and three cats: A novel CVC congenital malformation - Spediacci, Carlotta; Longo, Maurizio; Specchi, Swan; Pey, Pascaline; Rabba, Silvia; Mavraki, Eirini; Di Giancamillo, Mauro; Panopoulos, Ioannis (Frontiers in Veterinary Science, 2022)
Transcaval ureter is a rarely reported human congenital malformation of the pre-renal segment of the inferior vena cava (IVC) not yet reported in veterinary medicine. The objective of this multicenter retrospective case series study was to describe the computed tomography (CT) features of transcaval ureters in dogs and cats. Patients referred for pre- and post-contrast CT exam of the abdomen and presenting this abnormality were retrospectively included. Multiple qualitative features were described for each ureteral abnormality detected. Three cats and two dogs with transcaval ureter were identified consisting in a segmental duplication of the CVC at the pre-renal level creating a vascular ring through which the ureter extended, identified as a double-barrel gun sign. The malformation was divided in two types according to the symmetry of the caval branches and location in relation with the aorta: type I symmetrical branches and right-lateral to aorta, type II asymmetrically branches and right-dorsal to aorta. In one case the malformation was associated with hydroureter and mild pyelectasia. In three cases, the anomaly was incidental and in the remaining two cases the clinical significance was uncertain. This is the first study describing the presence of transcaval ureter in dogs and cats. Computed tomography was a suitable method for the diagnosis of transcaval and a focal double-barrel gun sign of the CVC is proposed as the hallmark feature of this anomaly. The clinical relevance of this congenital vascular malformation is unclear and needs to be further investigated.